Penguatan Literasi Keuangan Syariah melalui Lembaga Keuangan Syariah sebagai Upaya Pencegahan Praktik Fintech Ilegal di Indonesia. - Zahra, Salsabila; Eko Ribawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the role of Sharia Financial Institutions (SFIs) in strengthening sharia financial literacy as a preventive measure against illegal online lending practices in Indonesia. The study uses a descriptive qualitative method through literature review and normative legal analysis of fintech regulations (POJK 77/2016, PBI 19/12/PBI/2017, PDP Law 27/2022, and DSN-MUI Fatwa 117/2018) as well as various studies related to Islamic financial literacy, the role of LKS, and the phenomenon of illegal online lending. The results of the analysis show that Islamic financial literacy still lags behind conventional financial literacy, while the educational and social roles of LKS have not been fully utilized. On the other hand, the legal framework for fintech is adequate, but weak in terms of implementation and public literacy. This study recommends strengthening LKS literacy strategies based on community and digital platforms and developing Islamic microfinance as a safer alternative to illegal online loans.